Diseño de un centro de día y residencia geriátrica en el Cantón Ambato” - Alexander Daniel CortÈz Valverde (2024)
The research highlights the importance of architectural design in improving the quality of life of older adults in Ambato, Ecuador, in response to global population aging. It focuses on the urgent need for spaces designed specifically for this segment, applying the principles of Healthy Architecture to enhance their well-being. By investigating the specific needs of the elderly in Amba-to, an integrated design is proposed for a day center and a geriatric residence. This design is based on an analysis that incorporates global trends and local requirements, prioritizing elements that ensure functionality, comfort and well-being. The proposal pro motes an inclusive and ergonomic design approach, incorporating biophilic concepts to link spaces with the natural environment, which guarantees accessibility and promotes environ mental sustainability. This approach favors social inclusion and environmental responsibil ity, highlighting the need to adopt architectural practices focused on the well-being of older adults. It contributes to the debate on how architecture can adapt to the needs of an aging population, promoting environments that support an active, dignified and healthy life. This study highlights the importance of creating spaces that not only satisfy physical needs, but also strengthen the sense of community and emotional well-being, in line with the objectives of general well-being and sustainability. The research demonstrates how careful and con scious design can transform the lives of older adults, offering architectural solutions that re flect respect, care and appreciation towards them, thus ensuring an optimal quality of life.